The Influence of Competence, Training and Employee Placement in Em-ployee Performance in Technical Executive Unit of Regional Finance Agen-cy, Bangka Belitung Islands Province, Bangka Regency - Muhammad Yusuf Khalied Mufti; Reniati Reniati; Hamsani Hamsani (Jurnal Ekonomi Dan Statistik Indonesia, 2021)
The research was motived by the existing condition showing that employees have not been able to work optimally in a government agency. This study aimed to analyze and examine the influence of competence, training, and employee placement on employee performance in the Technical Executive Unit of Regional Financial Agency of Bangka Belitung Islands Province, Bangka Regency. This study is descriptive research. The method used was the quantitative research method because the data obtained was in the form of numbers derived from questionnaires. The number of samples was 44 respondents generated by the saturated sample method. The analysis model utilized multiple linear regression, with the t-test, f-test, and coefficient of determination. Based on multiple linear regression analysis found Y = 8,669 + 0,283 X1 + 0,447 X2 + 0,256 X3. Based on the results of research on competence, training and employee placement partially have a positive and significant effect on the performance of the employee of the Regional Finance Office of Bangka Regency, Bangka Belitung. Based on the results of the simultaneous test, it is known that competence, training and employee placement together have a significant effect onthe performance of the employees, while the results of the analysis of the coefficient of determination (R2) show the determination of R2 in this study is 76% and there are still 24% of other variables outside the study that can still be developed for further research.